O conceito de pessoa no Concílio Vaticano II - Vaccarello, Gabriel Lopes (2022)
The present work has as its theme the concept of person of the Second Vatican Council, trying to extract the concept of paragraph number 12 of the Pastoral Constitution. Taking into account that the paragraph is divided into three essential parts, the research is developed around the three core themes of each of the parts of the paragraph, namely: the various discussions, throughout history, about the concept of the human person who ends up for defining man in a wrong way and therefore directing him to a purpose that does not match who he really is; the very definition of man that passes through the concept of imago Dei, having to define, therefore, the meaning of being the image and likeness of God; and, finally, the human person as created for the communion and sharing of life. The main objective of the work is to investigate the concept of person, so that, after a definition of what it means to be a person according to the imago Dei, this concept can be applied to the theme of the family, a greater expression of what the communion of persons means. The research was developed under an inductive method, investigating texts and authors that contributed to the development of the central theme of the work and on the application of the concept to the family nucleus and the matrimonial reality. Finally, it should be noted that the research highlights the need for God's participation in family life, which requires the sacramentality of marriage, as a prerogative for the true correspondence of the meaning of marriage and the family